2000
DOI: 10.1182/blood.v96.5.1756.h8001756_1756_1763
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis is rapidly triggered by antisense depletion of MCL-1 in differentiating U937 cells

Abstract: Mcl-1 is a member of the Bcl-2 protein family, which has been shown to delay apoptosis in transfection and/or overexpression experiments. As yet no gene knockout mice have been engineered, and so there is little evidence to show that loss of Mcl-1 expression is sufficient to trigger apoptosis. U937 cells constitutively express the antiapoptotic protein Bcl-2; but during differentiation, in response to the phorbol ester PMA (phorbol 12 β-myristate 13 α-acetate), Mcl-1 is transiently induced. The purpose of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…However, it selectively targets BCL2 but not MCL1. This may confer resistance to this drug, since MCL1 can compensate for the loss of BCL2 function (Moulding et al, 2000). Consistent with this, down-regulation of MCL1 increases the lethality of the BCL2 inhibitor ABT-737 in human leukaemia cells (Chen et al, 2007).…”
Section: Discussionmentioning
confidence: 68%
“…However, it selectively targets BCL2 but not MCL1. This may confer resistance to this drug, since MCL1 can compensate for the loss of BCL2 function (Moulding et al, 2000). Consistent with this, down-regulation of MCL1 increases the lethality of the BCL2 inhibitor ABT-737 in human leukaemia cells (Chen et al, 2007).…”
Section: Discussionmentioning
confidence: 68%
“…Several studies have shown that Mcl-1 plays a critical role in the survival of malignant cancers. 29,30 Indeed, Mcl-1 downregulation may be a critical mechanism for the anticancer activity of many synthetic chemicals. 18,31,32 Our group also recently reported that knockdown of Mcl-1 by tolfenamic acid or Mcl-1 siRNA clearly induced apoptosis in the YD15 MEC cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Mcl-1 phosphorothioate antisense oligonucleotides to Mcl-1 (AS) and control inverted antisense oligonucleotides (INV) were synthesized by Intergrated DNA Technology, Inc. The sequences employed were described previously as Mcl-AS-8 and MclinvAS-8 24. Primary macrophages were incubated with either Mcl-1 AS or INV (100 μM) for 24 h, then harvested, and examined for Mcl-1 expression by Western blot analysis and apoptosis by determination of subdiploid DNA content.…”
Section: Methodsmentioning
confidence: 99%